ANGKRINGAN MODERN ALA GEN Z : KREATIVITAS DAN ADAPTASI PENGEMBANGAN BISNIS DI ANGKRINGAN BERONDONG COFFEE RANTAU PRAPAT - Muhammad Ridho Efryanda; Nadira Aulia Zahra; Nazwa Akhiela Salsabila Batubara; Nabila Nabila; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the creativity and business adaptation carried out by Angkringan Berondong Coffee as a form of modern angkringan innovation targeting the Gen Z segment. The research approach used a qualitative descriptive method through observation, short interviews, and documentation. The results of the study show that Berondong Coffee is able to combine the concept of traditional angkringan with a modern style through space design, varied menus, digital marketing strategies, and the use of cashless payment technology. These findings show that the success of modern angkringan is not only determined by menu innovation, but also by the ability to understand Gen Z preferences that demand comfort, aesthetics, and speed of service. This research is expected to contribute to the development of culinary SMEs based on creativity and innovation, as well as emphasize the importance of understanding digital lifestyles, community engagement, and the ability to adapt to trends in order to remain competitive in running a sustainable business amid competition.